La formazione delle parole nell’italiano del Duecento: Osservazioni e proposte di analisi di alcuni nomi deverbali - Bisetto, Antonietta (Verbum – Analecta Neolatina, 2002)
This paper deals with the deverbal nominalisations with the suffixes -tore, -ione, -mento found in (a small corpus of texts of) the Fiorentino of the XIII century. The analysis is carried out from a synchronic point of view and tries to describe the word formation procedures adopted during the Duecento.